Plant kleptomaniacs: geographical genetic patterns in the amphi-apomictic Rubus ser. Glandulosi (Rosaceae) reveal complex reticulate evolution of Eurasian brambles - Sochor, Michal; Šarhanová, Petra; Duchoslav, Martin; Konečná, Michaela; Hroneš, Michal; Trávníček, Bohumil (Annals of botany, 2024)
BACKGROUND AND AIMS: Rubus ser. Glandulosi provides a unique model of geographical parthenogenesis on a homoploid (2n = 4x) level. We aim to characterize evolutionary and phylogeographical patterns in this taxon and shed light on the geographical differentiation of apomicts and sexuals. Ultimately, we aim to evaluate the importance of phylogeography in the formation of geographical parthenogenesis. METHODS: Rubus ser. Glandulosi was sampled across its Eurasian range together with other co-occurring Rubus taxa (587 individuals in total). Double-digest restriction site-associated DNA sequencing (ddRADseq) and modelling of suitable climate were used for evolutionary inferences. KEY RESULTS: Six ancestral species were identified that contributed to the contemporary gene pool of R. ser. Glandulosi. Sexuals were introgressed from Rubus dolichocarpus and Rubus moschus in West Asia and from Rubus ulmifolius agg., Rubus canescens and Rubus incanescens in Europe, whereas apomicts were characterized by alleles of Rubus subsect. Rubus. Gene flow between sexuals and apomicts was also detected, as was occasional hybridization with other taxa. CONCLUSIONS: We hypothesize that sexuals survived the last glacial period in several large southern refugia, whereas apomicts were mostly restricted to southern France, whence they quickly recolonized Central and Western Europe. The secondary contact of sexuals and apomicts was probably the principal factor that established geographical parthenogenesis in R. ser. Glandulosi. Sexual populations are not impoverished in genetic diversity along their borderline with apomicts, and maladaptive population genetic processes probably did not shape the geographical patterns.
Keywords: fylogeografie; Parthenogenesis; biologická evoluce; ddRADseq; Phylogeography; Gene Flow; geographical parthenogenesis; introgression; Europe; Rubus subgen. Rubus; Asie; Evropa; Apomixis; genetická variace; Biological Evolution; apomixie; Genetic Variation; partenogeneze; private alleles; fylogeneze; tok genů; Asia; Rosaceae; Phylogeny